THE CHOICE OF METHODS FOR THE DETERMINATION OF MECHANICAL LOSSES IN THE TRACTION MOTORS DC AND RIPPLE CURRENT - Afanasov, A. M. (Science and Transport Progress, 2010)
The analysis of experimental methods for determination of mechanical losses of power in the hauling electric engines of direct current is presented.